The Correlation of EFL Students’ Speaking Anxiety and Their Speaking Performance - Thoriq Rizki Firis Manda; Lulus Irawati (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. This study is conducted to see if there is a significant correlation of the EFL students’ speaking anxiety and their speaking performance. It used quantitative research method with correlation research design. There were 36 eleventh grade students of MAN 2 Madiun, participating in this study. Data were collected through using a speaking test and a questionnaire of the students’ speaking anxiety. The speaking test was assessed by using Brown’s speaking assessment and the questionnaire was measured by using 1-5 Likert-scale. The questionnaire was adapted from Woodrow (2015) to investigate the students’ speaking anxiety. The data were analyzed using normality and Pearson correlation test of IBM SPSS (Statistical Package for the Social Science) version 22. The result shows that H0 is rejected and Ha is accepted. There is a significant correlation among two variables that they are strongly negative correlated. The speaking anxiety is affecting the students’ speaking performance. It simply can be said that the more anxious someone the worst speaking score they get. Keywords: Speaking Performance, Anxiety, Speaking Anxiety